Clinicopathological Study of Gallbladder Lesions: Two Years Study - Kumari, Geeta; Deshpande, K A; Roy, Sagarika (Annals of Pathology and Laboratory Medicine, 2018)
Background: Gallbladder is one of the most frequently surgically resected organs which stores and concentrates the bile and is involved by both non neoplastic as well as neoplastic diseases. Chronic calculous cholecystitis is the most common benign lesion of gallbladder and pain abdomen is the commonest clinical presentation. Both non neoplastic and neoplastic lesions have similar clinical presentation and overlapping radiological findings. Methods: Total 550 cholecystectomy specimens were received in pathology department. Grossly, formalin fixed specimens were examined carefully and section were given from neck, fundus and body of gallbladder. Whenever it was necessary, additional sections were given. After processing, the H&E stained sections were studied thoroughly. All the clinical details were taken from case papers. Result: The commonly seen non neoplastic lesions were chronic calculous cholecystitis (405 cases), chronic cholecystitis (85 cases), Acute on chronic cholecystitis with or without stones (18 and 3 cases), acute necrotizing cholecystitis (2 cases), eosinophilic cholecystitis (3 cases), follicular cholecystitis (3cases), lymphoplasmacytic cholecystitis (1case), xathogranulomatous cholecystitis (9 cases), cholesterosis (4 cases), mucocele of gall bladder (2 cases), adenomyomatosis (3 cases) and gallbladder cholesterol polyp with cholecystitis (2 cases). Among neoplastic lesions 1 case was adenoma with severe dysplasia and 9 cases were adenocarcinoma. Conclusion: Chronic calculous cholecystitis was the most common lesion and out of 9 cases of carcinoma, 7 cases were diagnosed incidentally. Therefore, histopathological evaluation plays a critical role in identifying incidental gallbladder carcinoma for proper management of patients.